Exact solitary solutions of an inhomogeneous modified nonlinear Schrödinger equation with competing nonlinearities - Kavitha, L.; Akila, N.; Prabhu, A.; Kuzmanovska-Barandovska, O.; Gopi, D. (Elsevier BV, 2011)
We employed both tanh and sine–cosine function methods to study the inhomogeneous modified nonlinear Schrödinger (IMNLS) equation and constructed its exact solitary solutions by using symbolic computation software. We compared the solutions obtained by both the methods.
Keywords: Nonlinear Schrödinger equation; Exact solutions; Solitons; Symbolic computation; Tanh method; Sine–cosine method